International Remittances and the Household : Analysis and Review of Global Evidence - Adams, Richard H., Jr. (World Bank, Washington, DC, 2012)
This paper examines the economic impact of international remittances on countries and households in the developing world. To analyze the country-level impact of remittances, the paper estimates an econometric model based on a new data set of 115 developing countries. Results suggest that countries located close to a major remittance-sending region (like the United States, OECD-Europe) are more likely to receive international remittances, and that while the level of poverty in a country has no statistical effect on the amount of remittances received, for those countries which are fortunate enough to receive remittances, these resource flows do tend to reduce the level and depth of poverty. At the household level, a review of findings from recent research suggest that households receiving international remittances spend less at the margin on consumption goods-like food-and more on investment goods-like education and housing. Households receiving international remittances also tend to invest more in entrepreneurial activities.